2020
DOI: 10.5114/ada.2019.86182
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in skin diseases as perceived by patients and nurses

Abstract: Introduction: The appearance of the skin and its appendages not only reflects the general body condition, but also exerts an effect on one's self-esteem and self-image, and the way he/she is perceived by the others. Aim: To analyse the quality of life (QOL) in dermatological diseases, assessed by the patients themselves and the nurses being their caregivers. Material and methods: The survey was completed by 300 patients diagnosed with various dermatological conditions; however, only the data from 281 surveys w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Mood improves in patients in proportion to the cure [30]. Anxiety and depression are present in a large number of patients with VLUs, which is directly correlated with the number of experienced venous ulcers [43][44][45].…”
Section: Survival Functionsmentioning
confidence: 99%
“…Mood improves in patients in proportion to the cure [30]. Anxiety and depression are present in a large number of patients with VLUs, which is directly correlated with the number of experienced venous ulcers [43][44][45].…”
Section: Survival Functionsmentioning
confidence: 99%
“…Studies have demonstrated that dermatological diseases can have a negative impact on the patient's selfesteem and QoL. (8)(9)(10) Therefore, this study intended to ascertain if there was a difference in the impact on the QoL of patients between these two groups of conditions. The Bahamas has a population of 402,825 people of which 49% are males and 51% are females.…”
Section: Introductionmentioning
confidence: 99%
“…Wrinkles, coarsening and changes in elasticity occur in the skin, while the frequency of some dermatological diseases increases and/or their presentations change (1). Skin lesions in visible areas such as the face and hands undeniably have considerable negative effects on people (3). It is known that skin diseases of the face, which is the most striking body part at first glance, and other visible areas, lead to increased emotional stress and psychosocial effects (4).…”
mentioning
confidence: 99%